EKSPERIMENTASI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DENGAN GUIDED NOTE TAKING (GNT) PADA MATERI PERSAMAAN GARIS LURUS DITINJAU DARI KEMAMPUAN BEKERJA SAMA SISWA KELAS VIII SMP/MTs NEGERI DI KOTA SURAKARTA TAHUN PELAJARAN 2013/2014 - Anggraini, Nindia Elisie; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this research were to investigate: (1) which of the TPS-GNT learning model, the TPS learning model, and the direct learning model results in a better mathematics learning achievement; (2) which of the students with high, mediun, and low team work have a better mathematics learning achievement; and (3) which of team work of the students result in a better learning achievement for each learning models; and (4) which of the TPS-GNT, TPS and direct learning models result in a better learning achievement for each level of team work of the students.This research used the quasi-experimental method. The population of this research was all students of the junior secondary schools in Surakarta in the academic year of 2013/2014. The samples of this research consisted of 288 students who were divided into three experiment groups. The three groups consisted of group 1, group 2, and group 3. Both of group 1 and group 2 consisted of 193 students whereas group 3 consisted of 95 students. The data of this research were gathered from test of learning achievement in mathematics, questionnaire, and documentation. The data were then analyzed by using umbalanced Two-way Analysis of Variance. According to the research results, it can be concluded: (1) the learning model of Modified TPS was better than that of the TPS and direct learning models while the learning model of TPS was better than the direct learning model; (2) the students with high team work had a better learning achievement than those with medium and low team work while the students with medium team work was better than the low team work; and (3) in each team work, student with high team work, medium team work, and low team work, Â the mathematics learning achievement of the students taught with TPS-GNT learning model, TPS learning model, and direct learning model was as good as that of those; (4) in each learning model, the TPS-GNT, TPS and direct learning models, the learning achievement of the student with high team work, medium team work, and low team work, was as good as that of those.Keywords: TPS-GNT learning model, TPS learning model, direct learning model, team work and learning achievement.